Al-Hijrah Mosque's Website-Based Management Information System for Events and Donations - Tommy Satrio Wichaksono; Erina Dwi Noviandri; Teuku Maulana Iqbal Khairy; Afri Yudha; Andi Susilo (Fakultas Teknik Universitas Darma Persada, 2026)
This study aims to design and develop a website-based information system to manage activities and donations at the Al-Hijrah Mosque. Previously, information was communicated through direct conversations or short messages, which proved ineffective for data retrieval, updates, and transparency. The system was developed using the Laravel framework, PHP, and MySQL database, applying the Model-View-Controller (MVC) pattern. System testing was conducted using the Black Box approach to evaluate overall functionality. The results indicate that the developed website successfully provides a public platform featuring announcements, activity schedules, donation progress, and verification statuses, while concurrently offering an administrative panel for comprehensive data management. This digital transformation effectively assists the mosque's administrators in managing activities and verifying donations more transparently and efficiently, thereby increasing congregational trust.